Processing of carbon reinforced thermoplastic pre-impregnated materials - Novo, P. J. (2016)
The aim of this work is to produce and optimize the processing of carbon fibres thermoplastic matrix pre-impregnated materials (towpregs and PCT´s). Pultrusion and heated compression moulding were the selected manufacturing methods for processing all carbon fibres thermoplastic matrix pre-impregnated materials into composite parts. The optimization of those processes was made by studying the influence of the most relevant processing parameters in the final properties of the produced carbon fibres thermoplastic matrix pre-impregnated materials and composites. The method of Taguchi / DOE (Design of Experiments) was used to achieve this aim as it allowed making more rational choices of processing windows. The composite relevant mechanical properties were determined and studied. The final composites were also submitted to SEM microscopy analysis.